DEVELOPMENT OF PROBLEM-BASED LEARNING-ASSISTED MATHEMATICS LEARNING TOOLS WITH SCIENTIFIC APPROACHES TO IMPROVE STUDENTS' CREATIVE THINKING SKILLS AND CONFIDENCE - ABIL MANSYUR; CHRISTIAN P. MANIK; BORNOK SINAGA (CV KULTURA DIGITAL MEDIA, 2021)
The purpose of this study was to determine the development of problem-based learning (PBL) based mathematics learning tools with a scientific approach to improve students' creative thinking skills and self-confidence (self-confidence) which are valid, practical and effective. Negeri 22 Medan is even semester of the 2019/2020 school year, while the object in this study is a learning device based on a scientific approach, the quadrilateral material was developed. The stages of this research are the stages of this research are the analysis stage, the planning stage (design). The development stage (develop) and the trial stage (validation). The results of this study indicate (1) the validity of the problem-based learning tools with the scientific approach developed including the valid category, with the average score of the experts obtained: RPP (4,565); Book Teacher (4,475); Student Book (4,508); Student Worksheets (4,474); (2) The problem-based learning device with the scientific approach developed is included in the practical category with the assessment of experts, it is found that: in the first trial it was 4.10 (very high / practical) and in the second trial it was 4.3 (very high / practical) ); the reliability of the instruments in the first trial was 98.53 (good) and in the second trial it was 98.20 (good). (3) Problem-based learning tools with a scientific approach developed by more than 80% of students gave a positive response to the learning tools developed.